2010
DOI: 10.1111/j.1469-7998.2010.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of new tetranucleotide microsatellite loci and assessment of genetic variation of giant panda in two largest giant panda captive breeding populations

Abstract: The giant panda Ailuropoda melanoleuca is a critically endangered species endemic to China. In order to carry out effective genetic management for the giant panda population, sufficient and reliable polymorphic genetic markers are required to provide essential information on the genetic diversity survey of this species. Seven new tetranucleotide microsatellite loci were isolated and characterized in this study and presented here as a tool for evaluating the genetic variation of giant pandas in the world's two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…It demonstrated that these markers developed in this study were effective in genetic diversity analyses. Moreover, the mean allelic richness of the Chengdu captive population in our study was much higher than Li et al [ 8 ] and Shen et al [ 7 ]. However, the level of heterozygosity was similar, which means that the loci developed in this study with a higher number of alleles.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…It demonstrated that these markers developed in this study were effective in genetic diversity analyses. Moreover, the mean allelic richness of the Chengdu captive population in our study was much higher than Li et al [ 8 ] and Shen et al [ 7 ]. However, the level of heterozygosity was similar, which means that the loci developed in this study with a higher number of alleles.…”
Section: Discussioncontrasting
confidence: 79%
“…In addition, the design of conservation strategies for the wild panda population is also limited by the lack of information on the population’s genetics. Although microsatellite loci analyses [ 3 - 8 ] have been used to assess the genetic variability and evaluate the population size for giant pandas, the genetic status of the giant panda is still matters of significant controversy. For example, some researchers assumed that wild populations might have low genetic variability [ 9 - 11 ], while Lu et al [ 3 ] and Zhang et al [ 5 ] concluded that wild populations might maintain high genetic variation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past several years, SSRs have been widely employed in genome mapping, forensics, population structure, phylogenetics, linkage, and kinship relationships (Dib et al, 1996;Selkoe and Toonen, 2006;Li et al, 2010). In addition, SSRs have been found in recent studies to serve a functional role affecting gene regulation, transcription, protein function, and genome organization (Kashi and King, 2006;Lawson and Zhang, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Microsatellite markers have become an important genetic markers in the field of molecular biology (Selkoe & Toonen, 2010 ) and have been widely used in population surveys (Creel et al, 2003 ; Piggott et al, 2006 ; Wang et al, 2016 ), genetic diversity assessments (Du et al, 2016 ; Li et al, 2010 ; Shen et al, 2010 ; Vanhala et al, 1998 ; Zhang et al, 2007 ), and genetic management of populations (Shan et al, 2014 ). The combined application of microsatellite markers, mitochondrial markers and noninvasive genetic sampling has contributed greatly to giant pandas conservation in the past 20 years, allowing giant panda population studies without the risk of capture stress, injury or death.…”
Section: Introductionmentioning
confidence: 99%